SVT and Gram Negative Sepsis in Neonates - Pathak, Om Krishna; Singh, Yengkhom Rameshwor; Purswani, Sunil; Suryawanshi, Pradeep (Journal of Nepal Paediatric Society, 2019)
Supraventricular tachycardia is the most common tachyarrhythmia seen in fetuses, neonates and infants. Sustained SVT may lead to congestive cardiac failure. Neonatal supraventricular tachycardia is more commonly associated with other cardiorespiratory and congenital problems and is uncommon in an otherwise healthy infant. Supraventricular tachycardia is also caused by neonatal sepsis but has rarely been reported. Here, we report two cases of SVT (Supraventricular tachycardia) induced by neonatal sepsis. Two neonates, one male and another female, both born to Indian mother had tachycardia with heart rate > 220 beats/minute along with poor perfusion, tachypnoea, fever and deranged coagulation profile. Both the babies had culture positive gram negative sepsis with normal echocardiography and supraventricular tachycardia on electrocardiograms which were treated with anti arrhythmic drugs and treatment of sepsis. This case report gives further insight into one more presentation and complication of neonatal sepsis.